Saudi Arabia : Financial Sector Assessment Program Update-Detailed Assessment of Observance of the CPSS Core Principles for Systemically Important Payment Systems. (IMF Staff Country Reports; Country Report ;, 2013)
This paper highlights the Saudi Arabia's Detailed Assessment of Observance of the Committee on Payment and Settlement Systems Core Principles for systemically important payment systems. The Saudi Arabian Monetary Agency (SAMA) is working to establish its payment system oversight function from an operational perspective. The power of SAMA to oversee the payment systems is stated in the central bank and banking laws. The powers of the central bank to operate, regulate, and oversee the payment systems are not detailed in the law and could be also covered by the proposed Payment System Law. Many critical aspects relating to the payment and securities settlement systems are covered in the legal framework.